Dynamic c‐Fos changes in mouse brain during acute and protracted withdrawal from chronic intermittent ethanol exposure and relapse drinking - Smith, Rachel J. (Addict Biol, 2019)
Alcohol dependence promotes neuroadaptations in numerous brain areas, leading to escalated drinking and enhanced relapse vulnerability. We previously developed a mouse model of ethanol dependence and relapse drinking in which repeated cycles of chronic intermittent ethanol (CIE) vapor exposure drive a significant escalation of voluntary ethanol drinking. In the current study, we used this model to evaluate changes in neuronal activity (as indexed by c‐Fos expression) throughout acute and protracted withdrawal from CIE (combined with or without a history of ethanol drinking). We analyzed c‐Fos protein expression in 29 brain regions in mice sacrificed 2, 10, 26, and 74 hours or 7 days after withdrawal from 5 cycles of CIE. Results revealed dynamic time‐ and brain region‐dependent changes in c‐Fos activity over the time course of withdrawal from CIE exposure, as compared with nondependent air‐exposed control mice, beginning with markedly low expression levels upon removal from the ethanol vapor chambers (2 hours), reflecting intoxication. c‐Fos expression was enhanced during acute CIE withdrawal (10 and 26 hours), followed by widespread reductions at the beginning of protracted withdrawal (74 hours) in several brain areas. Persistent reductions in c‐Fos expression were observed during prolonged withdrawal (7 days) in prelimbic cortex, nucleus accumbens shell, dorsomedial striatum, paraventricular nucleus of thalamus, and ventral subiculum. A history of ethanol drinking altered acute CIE withdrawal effects and caused widespread reductions in c‐Fos that persisted during extended abstinence even without CIE exposure. These data indicate that ethanol dependence and relapse drinking drive long‐lasting neuroadaptations in several brain regions.